Electrocardiographic patch devices and contemporary wireless cardiac monitoring - Fung, Erik; Järvelin, Marjo-Riitta; Doshi, Rahul N.; Shinbane, Jerold S.; Carlson, Steven K.; Grazette, Luanda P.; Chang, Philip M.; Sangha, Rajbir S.; Huikuri, Heikki V.; Peters, Nicholas S. (Frontiers in Physiology, 2015)
Cardiac electrophysiologic derangements often coexist with disorders of the circulatory system. Capturing and diagnosing arrhythmias and conduction system disease may lead to a change in diagnosis, clinical management and patient outcomes. Standard 12-lead electrocardiogram (ECG), Holter monitors and event recorders have served as useful diagnostic tools over the last few decades. However, their shortcomings are only recently being addressed by emerging technologies. With advances in device miniaturization and wireless technologies, and changing consumer expectations, wearable ‘on-body’ ECG patch devices have evolved to meet contemporary needs. These devices are unobtrusive and easy to use, leading to increased device wear time and diagnostic yield. While becoming the standard for detecting arrhythmias and conduction system disorders in the outpatient setting where continuous ECG monitoring in the short to medium term (days to weeks) is indicated, these cardiac devices and related digital mobile health technologies are reshaping the clinician-patient interface with important implications for future healthcare delivery.